2019
DOI: 10.1080/10749357.2019.1609182
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of backward walking unmasks mobility impairments in post-stroke community ambulators

Abstract: Background: While over half of stroke survivors recover the ability to walk without assistance, deficits persist in the performance of walking adaptations necessary for safe mobility in the home and community. One such adaptation is the ability to walk or step backward. Post-stroke rehabilitation rarely includes assessment of backward walking (BW) and BW deficits have not been quantified in post-stroke community ambulators. Objective: To quantify spatiotemporal and kinematic BW characteristics in post-stroke c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…This finding was similar to that reported in the previous study by Hsueh and colleagues 36. The stepping backward task assessed an uncommon pattern of walking, leading to an increased task difficulty, ie, stepping backward required postural balance and motor control to a greater extent than stepping forward 37. In addition, during “takes 3 steps backwards,” patients cannot use visual input to help control planning of foot placement 38.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding was similar to that reported in the previous study by Hsueh and colleagues 36. The stepping backward task assessed an uncommon pattern of walking, leading to an increased task difficulty, ie, stepping backward required postural balance and motor control to a greater extent than stepping forward 37. In addition, during “takes 3 steps backwards,” patients cannot use visual input to help control planning of foot placement 38.…”
Section: Discussionsupporting
confidence: 86%
“…36 The stepping backward task assessed an uncommon pattern of walking, leading to an increased task difficulty, ie, stepping backward required postural balance and motor control to a greater extent than stepping forward. 37 In addition, during "takes 3 steps backwards," patients cannot use visual input to help control planning of foot placement. 38 Similar to the previous study, 34,36 we found that "rolls onto side" was the easiest item.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we expected that the age-related differences of the neuromuscular control of gait would be greatly evidenced during backward walking. Indeed, several findings support the idea that backward walking may unmask mobility impairments in adult stroke patients [ 43 ], Parkinson disease [ 93 ], and in children with cerebral palsy [ 42 ]. By comparing older to young adults, greater adjustments of spatiotemporal gait parameters have been observed during backward than forward walking [ 2 , 31 , 52 ].…”
Section: Discussionmentioning
confidence: 77%
“…First, this test measures balance when changing direction of gait (forward, to right, to left and backward), an important skill when walking in the community. 33 Second, to perform the FSST the individual needs to move away from the base of support. Others balance tests like BBS and POMA-B (Performance-Oriented Mobility Assessment - Balance) require minimal movement outside the base of support.…”
Section: Discussionmentioning
confidence: 99%